Formation of glacier runoff on the northern slope of Tavan Bogd mountain massif based on stable isotopes data - D. V. Bantsev; D. A. Ganyushkin; K. V. Chistyakov; A. A. Ekaykin; I. V. Tokarev; I. V. Volkov (Лëд и снег)
This investigation is based on measurements of stable isotopes concentrations (δD and δ18О) in water, snow and ice samples. Glaciers are composed of ice, snow, and fi n of atmospheric origin. The isotopic composition of these components is different, so when melting they form the melted glacial water with different isotope characteristics. Summer precipitation contains the heaviest isotopes, but only a small part of them remains on the glacier. The average isotopic composition of glacier ice represents the average composition of precipitation that accumulates on it. However, snow and fi n of different seasons can occur on the glacier surface, the isotopic composition of which differs from the isotopic composition of glacier ice. At different times of the ablation season different parts of the glacier melt, therefore the isotopic composition of melt waters will be different. Differences in the isotopic composition of the major runoff-forming components on the Northern slopes of the massif Tabyn-Bogdo-Ola had been identified. A part of melting ice in the formation of the runoff on this massif is determined by estimation of the isotopic composition of snow, ice, and fi n on different glaciers of this region. The average δ18О of snow on the glacier surface is −11.9‰, and this snow can be attributed to the precipitation fallen in late spring or early summer. Measured average isotopic composition of precipitation (δ18О = −11.9‰) was compared with the online calculator of the isotope content in precipitation (OIPC). The isotopic composition of glacial melt waters on the Northern macro-slope in the middle of July 2015 (δ18О = −15.3‰) differs from the isotopic composition of the territory of the Mongolian part of the massif (δ18О = −17.4‰) obtained from results of the analysis of eight samples taken at different edges of the glaciers at the beginning of August 2013. Isotopic separation shows important role of summer snow in feeding the glacial rivers of the massif even in the middle of the ablation season, especially for glaciers in the central part of the massif. The role of seasonal snow in feeding the glacier streams depends on the morphological type of glacier. It is maximum for corrie glaciers and minimum for the valley ones.